2010
DOI: 10.1111/j.1467-6494.2010.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mediational Role of Parenting on the Longitudinal Relation Between Child Personality and Externalizing Behavior

Abstract: Building on prior cross-sectional work, this longitudinal study evaluated the proposition that maternal and paternal overreactive and authoritative parenting mediates the effect of child personality characteristics on externalizing behavior. Data from the Flemish Study on Parenting, Personality, and Problem Behavior were used in a moderated mediation analysis (N=434). Teachers rated children's Big Five characteristics, fathers and mothers rated their parenting, and 3 years later, children rated their externali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 59 publications
8
40
0
3
Order By: Relevance
“…Results showed no association of maladaptive personality traits with anxiety. Taken together, results in children with MID are similar to results of studies in a normal population in that lower scores on Compulsivity (Prinzie et al, 2003;Van Leeuwen et al, 2004), higher scores on Emotional Instability (Tackett, 2006) and Disagreeableness (Prinzie et al, 2010) are risk factors for developing behavioral problems, supporting the vulnerability model. These maladaptive personality traits may function as a diathesis by predisposing a child with MID for developing behavioral problems under specific circumstances.…”
Section: Maladaptive Personality Traitssupporting
confidence: 80%
See 3 more Smart Citations
“…Results showed no association of maladaptive personality traits with anxiety. Taken together, results in children with MID are similar to results of studies in a normal population in that lower scores on Compulsivity (Prinzie et al, 2003;Van Leeuwen et al, 2004), higher scores on Emotional Instability (Tackett, 2006) and Disagreeableness (Prinzie et al, 2010) are risk factors for developing behavioral problems, supporting the vulnerability model. These maladaptive personality traits may function as a diathesis by predisposing a child with MID for developing behavioral problems under specific circumstances.…”
Section: Maladaptive Personality Traitssupporting
confidence: 80%
“…However, previous research has mainly focused on the associations between behavioral problems and measures of adaptive personality traits. For example, research in representative community samples has identified consistent relationships between low Conscientiousness, low Agreeableness, high Extraversion and to a lesser extent high Neuroticism (Prinzie et al, 2003;Prinzie, Van der Sluis, De Haan, & Deković , 2010;Tackett, 2006;Van Leeuwen, Mervielde, Braet, & Bosmans, 2004) and behavioral problems. Given the importance of personality in the forthcoming DSM-V (Widiger, 2011;Widiger & Mullins-Sweatt, 2009) and the fact that maladaptive personality traits have not yet been studied in children with MID, the third aim of this study was to investigate the association of behavioral problems with maladaptive personality traits.…”
Section: Maladaptive Personality Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parenting practices which are associated with positive child development and encouraged through parenting programmes encourage an authoritative (firm but fair) parenting style (Hurlburt, Nguyen, Reid, Webster-Stratton, & Zhang, 2013). Authoritative fathering has been associated with a number of benefits for child well-being and development and has been shown to reduce the likelihood of the child developing problem behaviours (Prinzie, Van Der Sluis, De Hann, & Dekovic (2010).…”
Section: Introductionmentioning
confidence: 99%